Spontaneous Perforation of Pyometra - (:unkn) unknown (My University, 2006)
Pyometra is the accumulation of purulent material in the uterine cavity. Its reported incidence is 0.01 – 0.5 % in gynecologic patients; however, as far as elderly patients are concerned, its incidence is 13.6 % [3]. The most common cause of pyometra is malignant diseases of genital tract and the consequences of their treatment (radiotherapy). Other causes are benign tumors like leiomyoma, endometrial polyps, senile cervicitis, cervical occlusion after surgery, puerperal infections, and congenital cervical anomalies. Spontaneous rupture of the uterus is an extremely rare complication of pyometra. To our knowledge, only 21 cases of spontaneous perforation of pyometra have been reported in English literature since 1980. This paper reports an additional case of spontaneous uterine rupture.